KI-67 IMMUNOHISTOHEMICAL EXPRESSION IN PROSTATIC LESIONS (Iraqi Journal of Medical Sciences, 2017)
Background: The cell proliferation marker, ki-67, is a nuclear and nucleolar protein, which can be detected during all active phases of the cell cycle (G1, S, G2, and mitosis), but absent from cell resting phases. Thus, it considered as an excellent marker for determination the cell growth fraction and it has been detected to be a useful marker in predicting the development of human tumors.Objective: To evaluate the immunohistochemical expression of the antigen ki-67 in benign, pre-malignant and malignant prostatic lesions.Methods: A cross section study of 115 paraffin embedded prostatic tissue blocks, 76 cases were benign prostatic hyperplasia (BPH), 9 cases were high grade-prostatic intraepithelial neoplasia (HG-PI N), and 30 cases were prostatic carcinoma (PCa). Sections from each block were prepared for immunohistochemical staining of ki-67.Results: Ki-67, semi-quantiative evaluation, revealed that the majority of BPH (88.2%) and HG-PIN (66.7%) presented weak positivity (+), on other hand, the majority of PCa (60.0%) presented moderate positivity (++), and 16.7% showed intense positivity (+++). For prostatic carcinoma (PCa), no significant association had found between Ki-67 and serum tPSA level, while a significant association with Gleason grade was found, the higher grade (?7), the more intense positive immunolabeling for Ki-67.Conclusion: Significant differences between ki-67 immunolabeling and histological type of prostatic lesions, between BPH and HG-PIN, and prostatic carcinoma, which may have potential to evolve to malignancy.Keywords: BPH, HG-PIN, Ki-67, prostatic carcinoma, tPSACitation: Inas A. Rasheed, Alaa G. Hussein, Mohanad M. AbdulGhany. Ki-67 Immunohistohemical expression in prostatic lesions. Iraqi JMS. 2017; Vol. 15(2): 129-134. doi: 10.22578/IJMS.15.2.4
Keywords: BPH; HGPIN; Ki67; prostatic carcinoma; tPSA